The Effectiveness of Contextual Teaching and Learning to Increase Students' Self-Confidence and Higher-Order Thinking Skills in Economics Subject at SMA Negeri 1 Demak - Umam, Muhammad Fikrul; Melati, Inaya Sari (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2025)
This study examines the impact of the contextual teaching and learning (CTL) model in increasing students' self-confidence and higher-order thinking skills (HOTS) in Economics at SMA Negeri 1 Demak. Addressing challenges such as low self-confidence and limited critical thinking often associated with traditional teacher-centered methods, the research compares the CTL approach with Problem-Based Learning (PBL). Using a quasi-experimental design with a nonequivalent control group, the study involved 72 eleventh-grade students who were equally divided into an experimental group (employing CTL) and a control group (using PBL). Data was collected through direct observation of self-confidence indicators as well as pretest-posttest tests to measure HOTS based on aspects of analysis, evaluation, and creation. Statistical analysis, including observation sheet results, N-Gain score calculations, and Independent Sample t-Test, revealed significant improvements in both self-confidence and higher-order thinking skills among students in the CTL group compared to those in the control group. The findings indicate that the CTL model not only increases cognitive engagement but also fosters a more interactive and supportive classroom environment, ultimately enhancing academic performance in Economics. These findings support the adoption of the CTL model as an effective learning strategy in improving Economics subject outcomes at the high school level.